Outcomes of CT-Guided Deeper Localization Technique for Superficial Pulmonary Nodules - Wu, Jingpeng; Tian, Ye; An, Jianli; Zou, Zibo; Dong, Yanchao; Chen, Zhuo; Niu, Hongtao (The Thoracic and Cardiovascular Surgeon, 2023)
Background The possibility of coil dislocation in computed tomography (CT)-guided microcoil localization of superficial pulmonary nodules is relatively high. The aim of the study is to investigate the outcomes of deeper localization technique during CT-guided microcoil localization of superficial pulmonary nodules before video-assisted thoracoscopic surgery (VATS).Methods Fifty-seven identified superficial pulmonary nodules (nodule–pleural distance ≤ 1 cm on CT image) from 51 consecutive patients underwent CT-guided microcoil localization, and subsequent VATSs were included. The rate of technical success, complications, and excised lung volume were compared between deeper localization technique group and conventional localization technique group.Results The technical success rate of the localization procedure was 100% (25/25) in the deeper localization group and 81.3% (26/32) in the conventional localization group (p = 0.030). Excluding one case of lobectomy, the excised lung volume in the deeper localization group and the conventional localization group was 39.3 ± 23.5 and 37.2 ± 16.2 cm3, respectively (p = 0.684). The incidence of pneumothorax was similar between the deeper localization group and the conventional localization group (24.0 vs. 21.9%, respectively, p = 0.850). The incidence of intrapulmonary hemorrhage in the deeper localization group was higher (16.0%) than that in the conventional localization group (6.3%), but the difference was not statistically significant (p = 0.388).Conclusion CT-guided microcoil localization of superficial pulmonary nodules prior to VATS using a deeper localization technique is feasible. Deeper localization technique reduced the occurrence of dislocation but did not increase excised lung volume.
Keywords: computed tomography; CT scan; minimally invasive; lung cancer; treatment